Análisis del plan de construcción del puente para tubería sobre el río Virilla del AyA - De-la O-Arias, Josser Fernando (Instituto Tecnológico de Costa Rica, 2013)
Professional practice run was held at the Instituto Costarricense de Acueductos y Alcantarillados, the same was the analysis of the construction plan of the bridge over the river Virilla pipe. This analysis looks mainly study some important aspects from the point of view of construction and occupational safety, for it was necessary to refer to different standards, books and documents that helped create the framework for the study of the various topics, some international as, rules of the American Institute of Steel Construction, American Concrete Institute standards, standards of Occupational Safety and Health Administration. Within the national rules were consulted; Código Sísmico de Costa Rica 2010, Normas de seguridad en la construcción, Standards INTECO, among others. Within a few goals of this analysis include: Analyze the proposed construction plan for this work, comparing the mounting proposed main structure, analyze some sections of the structure, analyze the behavior of the cable and structure during assembly and review some aspects related to security. Finally is given to the Executive Unit of AyA a document with the results and analysis of the points studied, as well as a series of conclusions and recommendations consistent with the analyzes performed.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2013.
Keywords: Matriz de Riesgos; Código Sísmico de Costa Rica-2010; INTECO; AISC; ACI; Puente colgante